2013
DOI: 10.1007/s40263-012-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotic Augmentation Strategies in the Context of Guideline-based Care for the Treatment of Major Depressive Disorder

Abstract: There is a growing body of evidence that supports the use of atypical antipsychotics as augmentation agents for nonpsychotic unipolar major depressive disorder (MDD) in adults. Unfortunately, varying definitions of treatment-resistant depression, the limited evidence available for interventions after two or more treatment failures, and when and whether to use medications from nonantidepressant classes, remain a key gap in the knowledge base for clinicians. We identified and reviewed the following guidelines to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…There is no explanation for this association, except for assuming that ECT is usually used for schizophrenia with depressive symptoms, while certain SGA, such as quetiapine, olanzapine and aripiprazole, are also thought to be effective for these symptoms. 22,23 There are several limitations to this study. First, a number of variables, such as history of psychotropic drug treatment and response to antipsychotics, were not recorded.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is no explanation for this association, except for assuming that ECT is usually used for schizophrenia with depressive symptoms, while certain SGA, such as quetiapine, olanzapine and aripiprazole, are also thought to be effective for these symptoms. 22,23 There are several limitations to this study. First, a number of variables, such as history of psychotropic drug treatment and response to antipsychotics, were not recorded.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, patients receiving ECT were more likely to be prescribed SGA. There is no explanation for this association, except for assuming that ECT is usually used for schizophrenia with depressive symptoms, while certain SGA, such as quetiapine, olanzapine and aripiprazole, are also thought to be effective for these symptoms …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, four antipsychotic medications have received approval by the United States Food and Drug Administration (FDA) for use as an adjunct in inadequately treated major depressive disorder (MDD) or bipolar depression (these include quetiapine, olanzapine, aripiprazole, and lurasidone). It is important to note that the standard of care and treatment guidelines does not suggest that SGAs be used as first‐line agents for the treatment of depression (Patkar and Pae, ). This paper reviews the receptor profiles of SGAs that are useful in the treatment of depressive illness and presents three characteristics that are useful in utilizing these agents (Table ).…”
Section: Amine Receptors and The Behavioral Effects They Appear To Mementioning
confidence: 99%
“…Treatment options for patients with inadequate response to ADT include increasing the dose, switching to another ADT, adding a second ADT, or initiating adjunctive therapy with another medication such as an atypical antipsychotic [5,6]. A review of the evidence for antidepressant augmentation, combination, and switching strategies concluded that current data unequivocally support the use of certain atypical antipsychotics as a first-line option for augmentation in patients who failed first-line ADT [5].…”
Section: Introductionmentioning
confidence: 99%